CОMPАRАTIVE АNАLYSIS ОF CОNDITIОNАL EXPRESSIОNS (Neo Scientific Peer Reviewed Journal, 2026)
In the development of the development of our society in educational institutions, it is emphasized that the tasks of implementing trends in accelerating the areas of perfection of the educational system on the basis of digital technologies are needed. The circumstances of the upcoming series of programs and reforms are reflected. The methods of modernization, socio-economically sustainable development of the economy on the basis of industrial sectors , social economy, labor market requirements are reflected.